2023
DOI: 10.3390/land12111994
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Mining and Reclamation Practices Enhance Sustainable Land Use: A Case Study in Huainan Coalfield, China

Zhanjie Feng,
Zhenqi Hu,
Xi Zhang
et al.

Abstract: In the coal-grain composite area (CGCA) of eastern China with a high groundwater table (HGT), underground coal mining subsidence has caused extensive submergence of farmland, posing a significant threat to regional food security. Currently, land reclamation techniques in mining subsidence areas primarily focus on post-mining reclamation (PMR) of stable subsidence land with a low reclamation rate. This study investigated the application of concurrent mining and reclamation (CMR) technology for unstable subsiden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This technology advocates using mining subsidence control technology to excavate coal resources underground and implement reclamation measures on the surface before or during mining [4,26]. Relevant studies have shown that this technology can improve the land reclamation rate [4,18,[27][28][29]. This technique requires engineers to implement reclamation measures before cropland waterlogging occurs to salvage more soil.…”
Section: Introductionmentioning
confidence: 99%
“…This technology advocates using mining subsidence control technology to excavate coal resources underground and implement reclamation measures on the surface before or during mining [4,26]. Relevant studies have shown that this technology can improve the land reclamation rate [4,18,[27][28][29]. This technique requires engineers to implement reclamation measures before cropland waterlogging occurs to salvage more soil.…”
Section: Introductionmentioning
confidence: 99%
“…It is imperative to conduct research on sustainable postgold mining land rehabilitation, with the goal of minimizing losses arising from land degradation and maximizing land productivity. A suitable amelioration technology that aligns with site conditions can play a key role in enhancing soil fertility and land quality (Feng et al, 2023;Setiawan et al, 2021). Consequently, judicious stewardship of post-mining terrains is essential in attenuating detrimental environmental repercussions and advocating for sustainable mining protocols.…”
Section: Introductionmentioning
confidence: 99%